MODELING OF HEIGHT Tectona grandis L. f CLONAL AND SEMINAL - MOTTA, Alessandro Soares da; ALMEIDA, Everton José; VENDRUSCOLO, Diogo Guido Streck; SOUZA, Hudson Santos; MEDEIROS, Reginaldo Antonio; SILVA, Raiane Scandiane da (Brazilian Journal of Biometrics, 2016)
This study aimed to evaluate the linear and non-linear modeling to predict the total height of Tectona grandis L.f. trees (teak) in young stands of clonal origin and seminal in the municipality of Figueirópolis D'Oeste, Mato Grosso. Data collection was performed by forest census, at ages 36 and 48 months, and measured the diameter with bark 1.3 m height (dbh) and total height (h) of trees. It were evaluate six regression models subdivided into two categories: linear and non-linear estimation for the total height of teak. The criterion for selection of the models was in accordance with the highest adjusted coefficient of determination, lower standard error of estimate in percentage and graphical analysis of waste. The validation of the equation was made based on the chi-square test, with a significance level of 0.05. The linear models showed to be superior to non-linear for three of the four treatments evaluated. The hypsometric equations were validated and are recommended for estimation of teak tall in similar condition.